CuAAC ensembled 1, 2, 3-triazole linked nanogels for targeted drug delivery: a review. Issue 5 (18th January 2023) - Singh, Gurleen; Majeed, Ather; Singh, Riddima; George, Nancy; Singh, Gurjaspreet; Gupta, Sofia; Singh, Harminder; Kaur, Gurpreet; Singh, Jandeep
Abstract : Copper(i ) catalyzed alkyne azide cycloaddition is the quintessential example of 'Click Chemistry', provides an adaptable platform for the synthesis of nanogels for sustained drug release at targeted sites owing to their better biocompatibility. Abstract : Copper(i ) catalyzed alkyne azide cycloaddition (CuAAC), the quintessential example of 'click chemistry', provides an adaptable and adequate platform for the synthesis of nanogels for sustained drug release at targeted sites because of their better biocompatibility. The coupling of drugs, carried out via various synthetic routes including CuAAC, into long-chain polymeric forms like nanogels has exhibited considerable assurance in therapeutic advancements and intracellular drug delivery due to the progression of water solubility, evacuation of precocious drug release, and improved upthrust of the pharmacokinetics of the nanogels, thereby rendering them as better and efficient drug carriers. The inefficiency of drug transmission to the target areas due to the resistance of complex biological barriers in vivo is a major hurdle that impedes the therapeutic translation of nanogels. This review compiles the data of nanogels synthesized specifically via CuAAC 'click' methodology, as scaffolds for targeted drug delivery and their assimilation into nanomedicine. In addition, it elaborates the ability of CuAAC to graft specific moieties and conjugating biomolecules like proteins and growth factors, onto orthogonally functionalized polymer chains with various chemical groups resulting in nanogels that are not only more appealing but also more effective at delivering drugs, thereby enhancing their site-specific target approach and initiating selective therapies.